Fa'aliyyah Tatbīq Tharīqah Jam'iyyah Al'āb Al-Musābaqah (Teams Games Tournament) bisti'khdām Bithāqah Al-Suwar wa Al-Kalimāt li Tarqiyyah Mahārah Al-Kalām: The Effectiveness of Applying the Teams Games Tournament (TGT) Method Using Picture and Word Cards to Improve Speaking Skills - Siti Nurhayati (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2012)
Speaking skill is one of the language skills aimed to be achieved in Arabic language teaching. Speaking serves as the primary means to foster mutual understanding and reciprocal communication using language as the medium. Speaking activities should be engaging in language classes, but often the opposite occurs—these activities become uninteresting, fail to stimulate the situation, and the atmosphere becomes stagnant. This happens due to students' limited mastery of vocabulary and sentence patterns. However, the key to the success of such activities lies with the instructor. If the instructor can stimulate the learning environment, provide topics suitable for students' proficiency levels, and creatively develop learning models and methods, these obstacles can be overcome. One of the learning methods employed is the Teams Games Tournament (TGT), a cooperative learning model that is easy to implement by involving all students' activities without status differences. This method includes students' roles as tutors and incorporates game elements and reinforcement. The TGT learning model allows students to learn more relaxedly and fosters responsibility, cooperation, healthy competition, and learning engagement. The strategy used in teaching speaking skills includes the use of picture and word cards.